Different Airway Inflammatory Phenotypes Correlate with Specific Fungal and Bacterial Microbiota in Asthma and Chronic Obstructive Pulmonary Disease - Rui Yang; Qiao Zhang; Zhidong Ren; Hong Li; Qianli Ma (Journal of Immunology Research)
Background. Studies of chronic airway inflammatory diseases have increasingly focused on airway microbiota. However, the microbiota characteristics of asthma and chronic obstructive pulmonary disease (COPD) patients with different airway inflammatory phenotypes remain unclear. Objective. We aimed to reveal the differences of fungal and bacterial microbiota between eosinophilic asthma (EA) and noneosinophilic asthma (NEA) patients and between eosinophilic COPD (EC) and noneosinophilic COPD (NEC) patients. Further, explore whether similarities exist in the airway microbiota of patients with the same phenotype. Methods. Induced sputum samples were collected from 45 asthma subjects and 39 COPD subjects. The airway microbiota of the subjects was profiled by nearly full-length 16S rRNA and internal transcribed space (ITS) sequencing. Results. Subjects with eosinophilic phenotype (EA and EC) showed significant differences in both fungal and bacterial microbiota compared to the corresponding subjects with noneosinophilic phenotype (NEA and NEC). In addition, no differences were observed between the fungal microbiota of subjects with the same phenotype (EA vs. EC, NEA vs. NEC). In bacterial microbiota, the greater relative abundance of Streptococcus thermophilus was observed in EA and EC subjects, while Ochrobactrum was enriched in NEA and NEC subjects. In fungal microbiota, the EA and EC subjects showed higher relative abundances of Aspergillus and Bjerkandera, while the NEA and NEC subjects were enriched in Rhodotorula and Papiliotrema. Conclusions. Different airway inflammatory phenotypes were related to specific fungal and bacterial microbiota in both asthma and COPD, while the same airway inflammatory phenotype revealed a degree of similarity in airway microbiota, particularly in fungal microbiota.